2023
DOI: 10.3390/su15076228
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Sustainable Accessibility Mapping of Urban Parks: Evidence from the Second Largest Settlement of Sindh, Pakistan

Abstract: Hyderabad’s recreational amenities have made limited progress in comparison to the development of its industrial and commercial sectors. People require parks to unwind from their hectic lives. Parks can be a healthy location to host social events and can enhance community bonds. The evaluation of park accessibility has not been considered over the years in Hyderabad. Hyderabad is the eighth largest settlement in Pakistan and the second largest in the Sindh province. Thus, this study aimed to evaluate the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Socioeconomic factors (economic development, population density, and urbanization) also pose a considerable impact on LULC by changing land use for housing, agriculture, and industry (Seto, Guneralp, & Hutyra, 2012). Parks are also an important component of green urban landscapes bene ting the city's economy, ecology, and society (Khahro et al, 2023;Rigolon, 2016). Land use changes can also affect species composition, general ecological functioning, and connectivity.…”
Section: Gis (Geographical Informationmentioning
confidence: 99%
“…Socioeconomic factors (economic development, population density, and urbanization) also pose a considerable impact on LULC by changing land use for housing, agriculture, and industry (Seto, Guneralp, & Hutyra, 2012). Parks are also an important component of green urban landscapes bene ting the city's economy, ecology, and society (Khahro et al, 2023;Rigolon, 2016). Land use changes can also affect species composition, general ecological functioning, and connectivity.…”
Section: Gis (Geographical Informationmentioning
confidence: 99%
“…Even ordinary trips, like the purchase of grocery items from distinct locations, can take a longer travel time. However, research has shown that most people would like to spend less time while traveling to reach essential activities [65]. As travel demand increases, there is a rise in traffic congestion, which may put enormous pressure on accessibility parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accessibility and satisfaction evaluation is the most mature field, giving rise to successive analytical models based on spatial distance, time consumption, and spatio-temporal integration. For example, Khahro [47] and Semenzato [48] conducted case studies on spatial accessibility of urban parks in Pakistan and Italy using GIS tools and spatial distance modeling. Li [49] introduced the concept of time sensitivity on the basis of distance accessibility and analyzed the characteristics of the service radius and area of urban parks in Shanghai based on actual time consumption.…”
Section: Relationship Between Urban Park and Populationmentioning
confidence: 99%